Ode to the city - an ethnographic drama - Blackledge, Adrian 1959-; Creese, Angela 1959- (Multilingual Matters, 2022)
This ethnographic drama script is adapted from observations conducted in a large city centre library in the UK. It is a creative curation of field notes, transcripts, audio recordings, video recordings, conversations, and observations. The ethnographic drama tells a story of political tension in everyday life at a time of austerity